Impact of serum uric acid to high-density lipoprotein cholesterol ratio on short-term outcomes in acute decompensated heart failure: a cohort study in Jiangxi Province, China - Lu, Zihao; Jian, Guoan; Jiang, Kun; He, Shiming; Wang, Zhenyu; Wang, Juan; Lan, Houhui; Sheng, Guotai; Zou, Yang; Zhang, Shuhua (Frontiers in Endocrinology, 2025)
IntroductionAccumulating evidence suggests that both serum uric acid (UA) and high-density lipoprotein cholesterol(HDL-C) play critical roles in the pathogenesis of heart failure. This study aimed to investigate the association between the UA-to-HDL-C ratio(UHR) and short-term all-cause and cardiovascular mortality in patients with acute decompensated heart failure(ADHF).MethodsA total of 2,404 ADHF patients admitted to Jiangxi Provincial People’s Hospital from 2018 to 2024 were included in this study. The association between the UHR and 30-day all-cause and cardiovascular-specific mortality in patients with ADHF was systematically evaluated using Kaplan-Meier analysis, Cox regression, restricted cubic spline models, and stratified analysis. The robustness of the findings was further validated through multi-faceted sensitivity analyses.ResultsDuring the 30-day follow-up period, 156 patients(6.49%) died in the entire cohort, with 120 deaths attributed to cardiovascular causes. The all-cause mortality rates across UHR quartiles were as follows: Q1: 3.83%, Q2: 4.16%, Q3: 6.82%, Q4: 11.15%, while cardiovascular mortality rates were Q1: 2.33%, Q2: 3.49%, Q3: 5.32%, Q4: 8.82%. Multivariable Cox regression analysis revealed that each 1-unit increase in UHR was associated with a 30% increased risk of both all-cause and cardiovascular mortality in ADHF patients. Furthermore, compared with patients in the lowest UHR quartile, those in the highest quartile had an 88% increased risk of 30-day all-cause mortality and a 113% increased risk of cardiovascular mortality. Further restricted cubic spline regression analysis demonstrated a linear positive association between UHR and the 30-day risks of all-cause and cardiovascular mortality in ADHF patients. Stratified analysis revealed that the association between UHR and mortality in ADHF patients was not modified by age, gender, New York Heart Association classification, left ventricular ejection fraction, or comorbidities. Finally, multiple sensitivity analyses conducted across four dimensions—population heterogeneity, causal temporality, model adjustment, and data integrity—confirmed the robustness of the primary findings.DiscussionIn this cohort study conducted in Jiangxi, China, we demonstrated for the first time that the UHR could serve as a tool for early prognostic assessment of short-term all-cause and cardiovascular mortality risk in ADHF patients, and elevated UHR levels were independently associated with an increased risk of both outcomes.